Capicua Regulates Dendritic Morphogenesis Through Ets in Hippocampal Neurons in vitro - Li, Keqin; Shao, Shuai; Ji, Tongjie; Liu, Min; Wang, Lufeng; Pang, Ying; Chen, Mu; Xu, Siyi; Zhang, Kuiming; Wang, Qi; Zhuang, Zhongwei; Wei, Liang; et al. (Frontiers in Neuroanatomy, 2021)
Capicua (Cic), a transcriptional repressor frequently mutated in brain cancer oligodendroglioma, is highly expressed in adult neurons. However, its function in the dendritic growth of neurons in the hippocampus remains poorly understood. Here, we confirmed that Cic was expressed in hippocampal neurons during the main period of dendritogenesis, suggesting that Cic has a function in dendrite growth. Loss-of-function and gain-of function assays indicated that Cic plays a central role in the inhibition of dendritic morphogenesis and dendritic spines in vitro. Further studies showed that overexpression of Cic reduced the expression of Ets in HT22 cells, while in vitro knockdown of Cic in hippocampal neurons significantly elevated the expression of Ets. These results suggest that Cic may negatively control dendrite growth through Ets, which was confirmed by ShRNA knockdown of either Etv4 or Etv5 abolishing the phenotype of Cic knockdown in cultured neurons. Taken together, our results suggest that Cic inhibits dendritic morphogenesis and the growth of dendritic spines through Ets.